EMPLOYABILITY OF TEACHERS WHO APPLY THE METACAFÉ READER STRATEGY AT THE RICARDO PALMA UNIVERSITY - Romani Miranda, Úrsula (2020)
This bibliographic review article consists of observing and describing the employability of teachers who apply the Metacafé Lector strategy, at Ricardo Palma University. Employability presents different indicators such as the update of the professional who must be at the forefront of the changes and evolution of the new generations and, who in his role of said process, must seek to solve academic weaknesses. Actually, it is about students sitting in a better learning environment - teaching thus complying with the competencies established in the syllables. And, all this is evident among the colleagues and authorities of the university. The general objective of the research is to interpret the employability of the teachers who apply the strategy in question.